ผลกระทบของการใช้มาตรฐานการบัญชีไทยที่มีต่อธุรกิจพัฒนาอสังหาริมทรัพย์ ที่จดทะเบียนในตลาดหลักทรัพย์แห่งประเทศไทย - แอนนา ดีอุดมวงศา (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
To compare Thai Accounting Standards (TAS) with International Accounting Standards (IAS), and compare before and after changes of Thai Accounting Standards in 1998 including 7 major areas : accounting framework, inventory, property plant and equipment, impairment of assets, investment in subsidiary and associates, and segment report ; to investigate whether any problems arise from the application of such amended standards ; and to study the impacts of applying such standards on investments in Thai capital market, using available data of listed companies included only in the property sector. The study used SPSS as a tool for statistical test, including Paired-Simple T-Test and Independent-Sample T-Test for analysing data. The results of the study are divided into two parts. Part one includes the study of the stock volume trading response rate associated with those securities listed in the property sector. The results indicate that the trading volume of such securities during the year 1996-1997 is no less than that of 1999-2000. Part two focuses on the study of the average level of satisfaction toward Thai Accounting Standards. It was found that the existing standards on the accounting for investment in subsidiary and consolidated financial statements, investment in associates and segment reporting satisfied the users to a greater degree than those in use prior to the amendment. Additionally, the existing accounting standards on property, plant and equipment satisfied this the same group of users to a lesser degree than those in use prior to the amendment. Finally, the result of the study suggests that the existing standards are fairly good